Karakterisasi fenotip kultivar padi tahan dan rentan wereng coklat, Nilaparvata lugens Stål. (Hemiptera: Delphacidae) - Puji Astuti; Supriyadi Supriyadi; Supriyono Supriyono (Jurnal Entomologi Indonesia, 2012)
The brown planthopper, Nilaparvata lugens Stål. is a destructive and widespread insect pest throughout the rice areas in Indonesia. Rice plant resistance is an effective method in controlling N. lugens. However, the resistance sources and how their mechanism for imparting induced resistance against brown planthopper remains to be nderstood. This research was aimed to identify plant hair and protein banding patterns, as a genetic expression, of resistant and susceptible varieties. Identification of the variation of number of plant hair were carried out by using binocular microscope, while the protein banding patterns was detected by separation on SDS-Page. Co-variants analysis was adopted to identify the groups of resistant cultivars based on protein banding patterns. The results showed that plant hair on resistant rice cultivars are different with susceptible cultivars (resistance to Pelita I/1). The plant hair on resistant cultivars are larger/longer, more abudant and grew tighter than on susceptible cultivar. However the number of plant hair have no correlation with resistance level. In the absence of brown plant hopper infestation, the expression of protein total of resistant and susceptible cultivars are not clearly separated. Pelita I/1 varieties showed a similar banding pattern to IR 26 (biotype 1), IR 42 (resistance to biotype 2) and IR IR 74 (resistance to biotype 3), but the four cultivars are not similar to the resistant cultivar IR 36 varieties (resistance to biotype 2). Our research showed that both plant hair and protein banding patterns can not be used to identify the plant resistance.